HUBUNGAN KONDISI EKOSISTEM KEBUN KAKAO TERHADAP TINGKAT SERANGAN HAMA HELOPELTIS SP (Hemiptera:Miridae) - Sri Wahyuni; Walburga Anita Reri (Agriculture Faculty of Flores University, 2022)
This study aims to determine the population, intensity of attack of Helopeltis sp, and the relationship of the cocoa plantation ecosystem to the level of attack of Helopeltis sp. P3S. The study was conducted from May to June 2020. The variables observed were population and intensity of Helopeltis sp attacks as well as temperature, humidity, and natural enemies. The results showed that the population and intensity at the two locations were different. The number of Helopeltis sp in cocoa plantations that did not apply P3S was 49 individuals/tree with attack intensity ranging from 0 - 81.25%, The number of Helopeltis sp in cocoa gardens applying P3S was 6 individuals/tree with attack intensity ranging from 0 - 43.75%. The main factors that play an important role are temperature, humidity, and natural enemies.